KARAKTERISTIK MINYAK PRODUK PENCAIRAN BATUBARA MUDA DARI LATI, KALIMANTAN TIMUR - Hartiniati, Hartiniati (Jurnal Energi dan Lingkungan (Enerlink), 2007)
Liquefied coal contains of higher aromatic compound, nitrogen, oxygen andsmaller amount of sulfur compared to petroleum fuel oil. These componentscauses gum/sludge formation which disturbs product stability duringtransportation and storage. High aromatic content lowers the cetane number ofliquefied coal oil. The study suggests that the catalytic hydrotreating of liquefiedcoal oil produced from Lati coal liquefaction can reduce the amount of S, O, andN heteroatom significantly. Gas oil fraction derived from Lati coal has a cetaneindex = 38.6, while the octane number of naphtha is expected to be higher than95 through catalytic reforming. In general, it can be concluded that synthetic fueloil derived from Lati coal has the qualification as transportation fuel oil throughthe application of Improved BCL Process.Kata Kunci: limonite catalyst, coal liquefaction, catalytic hydrotreating, liquefiedcoal oil, gas oil fraction, cetane index, octaen number